2016
DOI: 10.1164/rccm.201512-2424oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway Microbiota Determines Innate Cell Inflammatory or Tissue Remodeling Profiles in Lung Transplantation

Abstract: The crosstalk between bacterial communities and innate immune cells potentially determines the function of the transplanted lung offering novel pathways for intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 36 publications
3
111
0
1
Order By: Relevance
“…47 In another set of studies from 112 patients post-lung transplantation, it was observed that a shift away from a Prevotella -dominant airway microbiome correlated with the development of inflammatory or remodeling profiles in macrophages. 46 Prevotella -high and -low community profiles have been noted in healthy subjects, 14,30 with the Prevotella- high profile being associated with enhanced “subclinical” lung inflammation, that is notable for enhanced expression of inflammatory cytokines and elevated Th-17 lymphocytes. 30,52 However, association studies do not determine the direction of causality and this data would be very consistent with a model where subclinical airway inflammation leads to higher levels of micro-aspirated Prevotella .…”
Section: Lung Microbiota and Immunitymentioning
confidence: 98%
See 2 more Smart Citations
“…47 In another set of studies from 112 patients post-lung transplantation, it was observed that a shift away from a Prevotella -dominant airway microbiome correlated with the development of inflammatory or remodeling profiles in macrophages. 46 Prevotella -high and -low community profiles have been noted in healthy subjects, 14,30 with the Prevotella- high profile being associated with enhanced “subclinical” lung inflammation, that is notable for enhanced expression of inflammatory cytokines and elevated Th-17 lymphocytes. 30,52 However, association studies do not determine the direction of causality and this data would be very consistent with a model where subclinical airway inflammation leads to higher levels of micro-aspirated Prevotella .…”
Section: Lung Microbiota and Immunitymentioning
confidence: 98%
“…It has been observed in a number of studies of humans and mice that the relative proportion of Gammaproteobacteria in the lungs increases during disease. 1,38,46 We have recently reviewed the role of inflammation in promoting the growth of P. aeruginosa in cystic fibrosis and inflamed airways. 38 Thus, one of the consequences of the upregulated host inflammatory response on mucosal surfaces is the production of terminal electron acceptors for anaerobic respiration that allow P. aeruginosa and other Gammaproteobacteria to grow, persist and outcompete all other microbial members on that surface.…”
Section: The Lung Microbiome and Inflammation: A Two-way Streetmentioning
confidence: 99%
See 1 more Smart Citation
“…However, significant gaps remain in our understanding of the dynamics of lung microbial communities and how these dynamics influence host-microbe interactions. Recent evidence in mice 54 and human subjects 55 argues for a cross-talk between microbes and immune cells, whereby inflammation can shape the microbiota and vice versa . 56 …”
Section: Asthmamentioning
confidence: 99%
“…Moreover, there is accumulating evidence that the immune state of the transplanted lung correlates with changes in the composition of the lung microbiota (Bernasconi et al, 2016;Charlson et al, 2012). High abundance of opportunistic pathogens such as members of the Staphylococcus and Pseudomonas genera have been linked to pro-inflammatory responses in the transplanted lung (Bernasconi et al, 2016;Erb-Downward et al, 2011), and also found in respiratory diseases such as COPD and asthma (Hilty et al, 2010;Mika et al, 2018). These bacteria activate macrophages and induce a strong inflammatory response after transplantation, reflected by high levels of tumor necrosis factor-α (TNFα) and cyclooxygenase-2 (COX2) (Bernasconi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%